Determination of the Percentage Ca(OH)2 Lime Stabilization Material for Weathered Clay Shale as Road Subgrade on Serang – Panimbang Toll Road Section III STA 57+200 - Sormin, Prince Joy; Satrya, Trihanyndio Rendy; Maulana, Mahendra Andiek; Supriyo, Wahyu (Journal of Infrastructure & Facility Asset Management, 2024)
Clay shale consists of thin, layered formations with irregular fractions, highly smooth, and easily separable along the layer planes. If Clay shale is exposed to sunlight, air, and water for a relatively short period, it will undergo weathering. The construction of the Serang - Panimbang Toll Road Section III is carried out by cutting the soil according to the planned contours. After the cutting process, the subgrade material undergoes a change in its characteristic properties and mechanics because the subgrade soil is Clay shale material that has weathered, commonly referred to as "Weathered Clay Shale." To transform this soil into a subgrade layer that meets the requirements, stabilization with Ca(OH)2 lime is necessary; in this case, the percentage of lime and the duration of curing need to be determined to achieve optimum lime content.The soil material used is Weathered Clay Shale obtained from the Serang - Panimbang Toll Road Section III STA 57+200. The research involves identifying the initial soil properties, conducting standard proctor tests on soil mixtures with lime variations of 4%, 7%, and 10% to determine the most optimum soil-lime mixture with Ca(OH)2. Subsequently, soil properties are identified with the most optimum lime mixture, and soaked CBR tests are conducted on the optimum lime-soil mixture with curing time variations of 0, 7, and 14 days.The 7% Ca(OH)2 lime mixture with weathered clay shale soil at STA 57+200 in the construction of the Serang-Panimbang Toll Road Section III has achieved sufficiently good bearing strength. The bearing capacity attained has exceeded the requirements of the Bina Marga Specifications Revision II, especially during the 14-day curing period, where the achieved bearing capacity significantly surpasses the specified standards.